Illuminating energy poverty: a case study of the energy needs and challenges of low-income households in De Aar, a renewable energy hub in South Africa’s Northern Cape Province - Borchardt, Stephanie Paula (2023)
Thesis (PhD)--Stellenbosch University, 2023.